Myeloid Angiotensin II Type 1 Receptor Mediates Macrophage Polarization and Promotes Vascular Injury in DOCA/Salt Hypertensive Mice - Yang, Xue-Feng; Wang, Huan; Huang, Yue; Huang, Jian-Hua; Ren, Hao-Lin; Xu, Qian; Su, Xiao-Min; Wang, Ai-Mei; Ren, Fu; Zhou, Ming-Sheng (Frontiers in Pharmacology, 2022)
Activation of the renin–angiotensin system has been implicated in hypertension. Angiotensin (Ang) II is a potent proinflammatory mediator. The present study investigated the role of myeloid angiotensin type 1 receptor (AT1R) in control of macrophage phenotype in vitro and vascular injury in deoxycorticosterone acetate (DOCA)/salt hypertension. In human THP-1/macrophages, Ang II increased mRNA expressions of M1 cytokines and decreased M2 cytokine expressions. Overexpression of AT1R further increased Ang II-induced expressions of M1 cytokines and decreased M2 cytokines. Silenced AT1R reversed Ang II-induced changes in M1 and M2 cytokines. Ang II upregulated hypoxia-inducible factor (HIF)1α, toll-like receptor (TLR)4, and the ratio of pIκB/IκB, which were prevented by silenced AT1R. Silenced HIF1α prevented Ang II activation of the TLR4/NFκB pathway. Furthermore, Ang II increased HIF1α via reactive oxygen species-dependent reduction in prolyl hydroxylase domain protein 2 (PHD2) expression. The expressions of AT1R and HIF1α and the ratio of pIκB/IκB were upregulated in the peritoneal macrophages of DOCA hypertensive mice, and the specific deletion of myeloid AT1R attenuated cardiac and vascular injury and vascular oxidative stress, reduced the recruitment of macrophages and M1 cytokine expressions, and improved endothelial function without significant reduction in blood pressure. Our results demonstrate that Ang II/AT1R controls the macrophage phenotype via stimulating the HIF1α/NFκB pathway, and specific myeloid AT1R KO improves endothelial function, vascular inflammation, and injury in salt-sensitive hypertension. The results support the notion that myeloid AT1R plays an important role in the regulation of the macrophage phenotype, and dysfunction of this receptor may promote vascular dysfunction and injury in salt-sensitive hypertension.